The Effects of Pre-feeding Oral Stimulations and Non-nutritive Sucking on Physical Growth and Independent Oral Feeding of Preterm Infants - Nasrin Khalessi; Sepideh Nazi; Mamak Shariat; Maryam Saboteh; Zahra Farahani (Mashhad University of Medical Sciences, 2015)
Background: Breastfeeding failures and oral feeding problems in preterm infants result in long-term health complications. In this study, therefore, we aimed to evaluate the effect of oral stimulation along with non-nutritive sucking (NNS) on independent oral feeding initiation and weight gain in preterm infants. Methods: This prospective randomized clinical trial was carried out at Aliasghar Hospital in Tehran, Iran, 2014. A total of 50 26-32 weeks gestational age hospitalized infants, who were fed through tubes, were recruited in the study. The newborns were randomized into A, B and C groups. In the A and B groups, the neonates were stimulated through oral stimulation as well as non-nutritive sucking for 5 or 10 days, while in the group C, no especial intervention was performed. Infants' mean daily weight gain, the number of days until initiation of oral feeding, oral feeding progression, the number of days until reaching full oral feeding and date of discharge were recorded. The obtained data were analyzed and compared in the three groups using SPSS version 16.0. Results: Of all the participants, 25 cases (55.55%) were male. Mean gestational age at birth and mean birth weight were 28.64±1.93 weeks and 1337.11±185.07 grams, respectively. In the group A, newborns' weight at reaching four and eight oral feedings per day and their weights at discharge were significantly higher than the other two groups (P=0.016, 0.001 and 0.001, respectively). Mean daily weight gain in the group A was higher (84.2850 g) than the other groups (69.5814 vs. 64.2677 g). However, ANOVA results showed that this difference was not significant (P=0.108). Moreover, independent samples t-test indicated that this difference between groups A and C was significant (P=0.049). Conclusion: In clinically stable preterm neonates, oral stimulation and should be implemented to increase their weight; however, further studies are required to address this issue.